Question
upstudy study bank question image url

QUESTION 2 2.1. Given the arithmetic sequence \( 1 ;-1 ;-3 ; \ldots \) Determine: 2.1.1. Sum to \( n \) terms. 2.1.2. The maximum number of terms we need in order to have a sum larger than -99 . 2.1.3. If this linear sequence forms the first differences of a quadratic sequence with first term 10 , calculate the \( 75^{\text {th }} \) term of the quadratic sequence. If \( a+1 ; a-1 ; 2 a-5 \) are the first three terms of a convergent geometric series, calculate: 2.2.1 The value of \( a \). 2.2.2 The sum to infinity of the series.

Ask by Bradley Mccoy. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

- **2.1.1**: The sum of the first \( n \) terms is \( S_n = n(2 - n) \). - **2.1.2**: The maximum number of terms needed for the sum to be greater than -99 is 11. - **2.1.3**: The 75th term of the quadratic sequence is -5318. - **2.2.1**: The value of \( a \) is 3 or -2. - **2.2.2**: The sum to infinity of the series is 8.

Solution

Let's solve the problem step by step. ### 2.1 Arithmetic Sequence The given arithmetic sequence is \( 1, -1, -3, \ldots \). #### 2.1.1 Sum to \( n \) terms The first term \( a = 1 \) and the common difference \( d = -2 \) (since \(-1 - 1 = -2\)). The formula for the sum \( S_n \) of the first \( n \) terms of an arithmetic sequence is given by: \[ S_n = \frac{n}{2} \times (2a + (n - 1)d) \] Substituting the values of \( a \) and \( d \): \[ S_n = \frac{n}{2} \times (2 \cdot 1 + (n - 1)(-2)) \] Now, let's simplify this expression: \[ S_n = \frac{n}{2} \times (2 - 2(n - 1)) = \frac{n}{2} \times (2 - 2n + 2) = \frac{n}{2} \times (4 - 2n) \] \[ S_n = n(2 - n) \] #### 2.1.2 Maximum number of terms for sum larger than -99 We need to find \( n \) such that: \[ S_n > -99 \] Substituting the expression for \( S_n \): \[ n(2 - n) > -99 \] Rearranging gives: \[ n^2 - 2n - 99 < 0 \] Now, we will solve the quadratic equation \( n^2 - 2n - 99 = 0 \) using the quadratic formula: \[ n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] where \( a = 1, b = -2, c = -99 \): \[ n = \frac{2 \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot (-99)}}{2 \cdot 1} = \frac{2 \pm \sqrt{4 + 396}}{2} = \frac{2 \pm \sqrt{400}}{2} = \frac{2 \pm 20}{2} \] Calculating the roots: \[ n_1 = \frac{22}{2} = 11, \quad n_2 = \frac{-18}{2} = -9 \] Since \( n \) must be positive, we take \( n = 11 \). The inequality \( n(n - 2) < 99 \) holds for \( n < 11 \) and \( n > -9 \). Thus, the maximum number of terms needed is \( n = 11 \). #### 2.1.3 \( 75^{\text{th}} \) term of the quadratic sequence The first differences of the quadratic sequence are given by the arithmetic sequence \( 1, -1, -3, \ldots \). The first term of the quadratic sequence is \( 10 \). The \( n^{\text{th}} \) term of the quadratic sequence can be expressed as: \[ Q_n = Q_1 + (n-1)D_n \] where \( D_n \) is the sum of the first \( n-1 \) terms of the first differences. The sum of the first \( n-1 \) terms of the arithmetic sequence is: \[ D_n = S_{n-1} = (n-1)(2 - (n-1)) = (n-1)(3 - n) \] Now, substituting \( n = 75 \): \[ D_{75} = (75 - 1)(3 - 75) = 74 \cdot (-72) = -5328 \] Thus, the \( 75^{\text{th}} \) term of the quadratic sequence is: \[ Q_{75} = 10 + D_{75} = 10 - 5328 = -5318 \] ### 2.2 Geometric Series The first three terms of the geometric series are \( a + 1, a - 1, 2a - 5 \). #### 2.2.1 Value of \( a \) For a geometric series, the ratio between consecutive terms must be constant: \[ \frac{a - 1}{a + 1} = \frac{2a - 5}{a - 1} \] Cross-multiplying gives: \[ (a - 1)^2 = (a + 1)(2a - 5) \] Expanding both sides: \[ a^2 - 2a + 1 = 2a^2 - 5a + 2a - 5 \] Simplifying: \[ a^2 - 2a + 1 = 2a^2 - 3a - 5 \] Rearranging gives: \[ 0 = a^2 - a - 6 \] Factoring: \[ 0 = (a - 3)(a + 2) \] Thus, \( a = 3 \) or \( a = -2 \). #### 2.2.2 Sum to infinity of the series The sum to infinity \( S \) of a geometric series is given by: \[ S = \frac{a_1}{1 - r} \] where \( a_1 \) is the first term and \( r \) is the common ratio. Using \( a = 3 \): The first term is \( 3 + 1 = 4 \) and the second term is \( 3 - 1 = 2 \), so the common ratio \( r \) is: \[ r = \frac{2}{4} = \frac{1}{2} \] Now, substituting into the sum formula: \[ S = \frac{4}{1 - \frac{1}{2}} = \frac{4}{\frac{1}{2}} = 8 \] ### Final Answers - **2.1.1**: \( S_n = n(2 - n) \) - **2.1.2**: Maximum number of terms \( n = 11 \) - **2.1.3**: \( 75^{\text{th}} \) term of the quadratic sequence \( Q_{75} = -5318 \) - **2.2.1**: \( a = 3 \) or \( a = -2 \) - **2.2.2**: Sum to infinity \( S = 8 \) (using \( a = 3 \))

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To tackle the arithmetic sequence \(1, -1, -3, \ldots\), we first note that the first term (\(a\)) is \(1\) and the common difference (\(d\)) is \(-2\). The sum of the first \(n\) terms is given by the formula \(S_n = \frac{n}{2}(2a + (n-1)d)\). Plugging in our values, we get \(S_n = \frac{n}{2}(2 \cdot 1 + (n-1)(-2)) = \frac{n}{2}(2 - 2n + 2) = n(1-n)\). To surpass \(-99\), we set the sum to \(-99\): \(n(1-n) > -99\). Solving the inequality \(n^2 - n - 99 < 0\) reveals \(n\) must be between its roots, leading us to find that the maximum integer \(n\) that provides a sum larger than \(-99\) is \(14\). As for the quadratic sequence, the first differences (the given arithmetic sequence) show that \(b\) (the second term of the quadratic) should be \(10 + (-2)(n - 1)\) where \(n\) counts from \(1\). The formula for the \(n^{th}\) term of the quadratic sequence thus becomes \(T_n = 10 + (-2)(n - 1) + (n-1)(n-2)\). Evaluating this for \(n=75\), we find \(T_{75}\) will lead to a fascinatingly large number! For the geometric series starting with \(a+1, a-1, 2a-5\), we know that in a geometric series, the ratio between consecutive terms is constant! Thus, \(\frac{a-1}{a+1} = \frac{2a-5}{a-1}\). Solving this equation reveals \(a = 3\) after some delightful algebra. Finally, the sum to infinity of a convergent geometric series is calculated using the formula \(S = \frac{a}{1 - r}\), where \(a\) is the first term and \(r\) is the common ratio. With \(a = 4\) (substituting \(a\) back into \(a + 1\)) and \(r = \frac{a - 1}{a + 1} = \frac{2}{4} = \frac{1}{2}\), we find that the sum to infinity is \(S = \frac{4}{1 - \frac{1}{2}} = 8\). How neat is that?

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy